PEMIKIRAN ETIKA POLITIK MUHAMMAD CHOLIL BISRI DALAM AL-DURR AL-RUMBÄ€NÄª - Irfan, Agus; Sarjuni, Sarjuni (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2020)
This article discusses the idea of Political Ethics from one of the Indonesian scholars named Muhammad Cholil Bisri in the Book of Al-Durr Al-RumbÄnÄ«. This study is under descriptive qualitative research using a socio-historical approach and sociology of knowledge that studies the interrelationships between thought and society. The results of this paper state that in Islam; the political problem is the area of ijtihÄdÄ« which has strong roots in Islam. The relationship between them can be called a mutually reinforcing symbiotic relationship (Ê»alÄqah indimÄjiyah). One of the influences of Islam in political traditions, for instance is its teachings on ethics that must inspire all policy issues. Even ethical configuration must also inspire the most important elements in the democratic political systems as called political parties. The term animates, explains that Islam as a system does not have to be realized in the form of formalization of sharÄ«a or political Islam movements. In addition to ethics, the goals that result from political dynamics must be in the form of benefit (maqá¹£ad al-siyÄsah). Therefore, political work carried out in the corridor of truth can be considered as worship and deliver the politician to the noblest profession in the sight of God.